Delayed Increase of Tyrosine Hydroxylase Expression in Rat Nigrostriatal System after Traumatic Brain Injury - Yan, Hong Qu (2006)
Tyrosine hydroxylase (TH) is the key enzyme for synthesizing dopamine (DA) in dopaminergic neurons and its terminals. Emerging experimental and clinical evidence support the hypothesis of a disturbance in dopamine neurotransmission following traumatic brain injury (TBI). However, the effect of controlled cortical impact (CCI) injury on TH in the nigrostriatal system is currently unknown. To determine if there is an alteration in TH after CCI injury, we examined TH levels at 1 day, 7 days, and 28 days post-injury by utilizing a commercially available antibody specific to TH. Rats were anesthetized and surgically prepared for CCI injury (4 m/sec, 3.2 mm) or sham surgery. Injured (n=6) and sham animals (n=6) were sacrificed and coronally sectioned (35 μm thick) through the striatum and substantia nigra (SN) for immunohistochemistry. Additionally, semiquantitative measurements of TH protein in striatal and SN homogenates from injured (n=6) and sham (n=6) rats sacrificed at the appropriate time post-surgery were assessed using Western blot analysis. TH protein is bilaterally increased at 28 days post-injury in nigrostriatal system revealed by immunohistochemistry in injured rats compared to sham controls. Western blot analysis confirms the findings of immunohistochemistry in both striatum and SN. We speculate that the increase in TH in the nigrostriatal system may reflect a compensatory response of dopaminergic neurons to upregulate their synthesizing capacity and a delayed increase in the efficiency of DA neurotransmission after TBI.